Media coverage and location choice - Kulchina, Elena (Strategic Management Journal, 2014)
Emphasizing the importance of informed location choice, prior strategy research has examined how private information about locations affects foreign direct investment. Publicly available media information has received little attention, however, perhaps because its impact on location choice is expected to be trivial. This study examines the relationship between the extent of a location's media coverage and the number of entering foreign firms in R ussia, using a novel instrumental variable for media coverage, a major anniversary of a city's establishment date. The results suggest that extensive foreign media coverage of a city increases the number of foreign entrants. This effect is stronger for firms with less private information about R ussian cities; i.e., more socially and geographically distant firms and foreign entrepreneurs. Copyright © 2013 John Wiley & Sons, Ltd .